New media poetics: contexts, technotexts, and theories - Morris, Adalaide Kirby. 1942-; Swiss, Thomas (The Mit Press, 2006)
Nuevos Medios Poética: Contextos, Technotexts y Teorías New media poetry poetry composed, disseminated, and read on computers exists in various configurations, from electronic documents that can be navigated and/or rearranged by their "users" to kinetic, visual, and sound materials through online journals and archives like UbuWeb, PennSound, and the Electronic Poetry Center. Unlike mainstream print poetry, which assumes a bounded, coherent, and self conscious speaker, new media poetry assumes a synergy between human beings and intelligent machines. The essays and artist statements in this volume explore this synergy's continuities and breaks with past poetic practices, and its profound implications for the future.By adding new media poetry to the study of hypertext narrative, interactive fiction, computer games, and other digital art forms, New Media Poetics extends our understanding of the computer as an expressive medium, showcases works that are visually arresting, aurally charged, and dynamic, and traces the lineage of new media poetry through print and sound poetics, procedural writing, gestural abstraction and conceptual art, and activist communities formed by emergent poetics.Contributors:Giselle Beiguelman, John Cayley, Alan Filreis, Loss Pequeño Glazier, Alan Golding, Kenneth Goldsmith, N. Katherine Hayles, Cynthia Lawson, Jennifer Ley, Talan Memmott, Adalaide Morris, Carrie Noland, Marjorie Perloff, William Poundstone, Martin Spinelli, Stephanie Strickland, Brian Kim Stefans, Barrett Watten, Darren Wershler-Henry.